Experimental model of distraction osteogenesis in edentulous rats - Maria Montserrat Pujadas Bigi; Marianela Lewicki; Angela Matilde Ubios; Patricia Monica Mandalunis (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Distraction osteogenesis (DO) is a surgical technique producing bone lengthening by distraction of the fracture callus. Although a large number of experimental studies on the events associated with DO of craniofacial skeleton have been reported, the few employing rat mandibular bone DO used complicated designs and produced a small volume of newly formed bone. Thus, this study aims to present an original experimental model of mandibular DO in edentulous rats that produces a sufficient quantity and quality of intramembranous bone. Eight male Wistar rats, weighing 75 g, underwent extraction of lower molars. With rats weighing 350 g, right mandibular osteotomy was performed and the distraction device was placed. The distraction device was custom made using micro-implants, expansion screws, and acrylic resin. Study protocol: latency: 6 days, distraction: ¼ turn (0.175 mm) once a day during 6 d, consolidation: 28 d after distraction phase, sacrifice. DO-treated and contralateral hemimandibles were dissected and compared macroscopically and using radiographic studies. Histological sections were obtained and stained with H&E. A distraction gap filled with newly formed and mature bone tissue was obtained. This model of mandibular DO proved useful to obtain adequate quantity and quality of bone to study bone regeneration.